On the question of calculating additional consumption of energy resources for the implementation of time make up in passenger traffic - K. M. Popov (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
The article discusses the features of definition of the energy component during time make up in passenger traffic. The total time of make up within the valuation section per month, especially in the summer, can reach very high values, therefore, segregation of energy component, associated with the make up, from total fuel consumption must be justified. This issue is also relevant in view of the fact that when rationing fuel and energy resources (FER) in passenger traffic component of consumption associated with time make up is considered alone. Thus network automated system for centralized processing of driver’s routes (CPDR), with which the valuation is made, based on the processing of driver’s routes, where a set of data on completed trips is limited. Determination of FER consumption for time make up with the use of software products that implement traction calculations requires actual speed data path in this trip. On-board system of registration of motion parameters, such as RMPAD (recorder of motion parameters and automatic driving) can act as the source of such data. However, there is currently no mechanism of data provision from RMPAD in CPDR, and in local RMPAD decryption systems in calculation of additional energy consumption for locomotive depot with time make up is not possible. To allow heating engineer set reasonable norms of fuel and energy resources for make up before solving the problem of integration of CPDR and RMPAD it is proposed for calculations to use the classical equation of the theory of traction, converted so that make up time could be among other input data.